New Institutionalism and Public Administration: A Review of Theories and Concepts - Sampaco-Baddiri, Nassreena (Philippine Journal of Public Administration, 2017)
While various social science disciplines have dominated the recent spate of scholarly work in institutionalism, the study of institutions itself is not new in public administration. The study of public organizations and institutions has highlighted legal structure and cognitive design as well as culture and norms in understanding organizational behavior, which has contributed to a bifurcated view of institutions as either formal or informal. New institutionalism highlights that while regulative formal institutions can serve as lamp posts to political, social and economic behavior, normative informal institutions can oftentimes encompass a wider institutional field beyond political jurisdictions. This paper looks at the evolution of institutionalism from a public administration perspective and provides an overview of how new institutionalism can be the lens to comprehend the fundamental issues of governance and development.
Keywords: Institutions, New Institutionalism, Formal Institutions and Informal Institutions